LIKUIDITAS, AKTIVITAS PERUSAHAAN, LEVERAGE PADA INDEKS PENGUNGKAPAN SUSTAINABILITY REPORT : BUKTI DARI PERUSAHAAN NON-KEUANGAN - Dhistianti Mei Rahmawantari (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study aims to examine the effect of Liquidity, Company Activity and Leverage on Sustainability Reports in Non-Financial Companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The data used in this research is quantitative data. The sampling technique using purposive sampling obtained a total sample of 104 data. The results of the study show that liquidity has no effect on the Sustainability Report. Company activities have a significant positive effect on sustainability report disclosure. Leverage has no effect on Sustainability Report disclosure. Liquidity, Company Activities, and Leverage affect the Sustainability Report